Global scale-free brain activity as a potential neural signature of visual information processing in aging. - Racz, Frigyes Samuel; Kaposzta, Zalan; Czoch, Akos; Chang, Joshua T.; Stylianou, Orestis; Mukli, Peter; Benge, Jared F.; Eke, Andras (Frontiers in Aging Neuroscience, 2026)
Introduction: Confluent evidence suggests that aging is associated with a reduction in the spectral slope of neural recordings. This phenomenon has been hypothesized to reflect an increase in the ratio of excitatory and inhibitory (E/I) balance. As neural E/I ratio is considered essential for cognitive functioning, this study investigated whether spectral slope (β) predicts cognitive performance in the older adults and could serve as a potential neural signature of cognitive aging. Nevertheless, few studies have examined how spectral slope estimates obtained from both eyes-closed (EC) and eyes-open (EO) resting states relate to cognitive performance in the aging population. Methods: To address this gap, this study analyzed electroencephalography (EEG) recordings of 19 community-dwelling elderly adults (CDE, aged between 60 to 80 years) and 24 young control individuals (YC, aged between 21 to 32 years) collected during EC and EO states. Further, β was estimated from global power spectra after separating scale-free from oscillatory components in the power spectrum. Results: Reduced β was observed in CDE in contrast to YC in both physiological states. While the YC group indicated an increase in β when transitioning from EC to EO, this change could not be observed in CDE. Finally, a strong, anticorrelated relationship between β in EO and performance on a rapid visual information processing task, was typically seen only in the CDE group. Discussion: These results potentially indicate an altered E/I ratio in the CDE cohort, while the inverse relationship with task performance suggests that this pattern could reflect a compensatory brain mechanism supporting cognition during aging.